The Oxford handbook of African archaeology - Mitchell, Peter 1962-; Lane, Paul (Paul J.) ([Oxford handbooks], 2013)
This handbook provides a comprehensive and up-to-date synthesis of African archaeology, covering the entirety of the continent's past from the beginnings of human evolution to the archaeological legacy of European colonialism. As well as covering almost all periods and regions of the continent, it includes a mixture of key methodological and theoretical issues and debates, and situates the subject's contemporary practice within the discipline's history and the infrastructural challenges now facing its practitioners. Bringing together essays on all these themes from over seventy contributors, many of them living and working in Africa, it offers a highly accessible, contemporary account of the subject for use by scholars and students of not only archaeology, but also history, anthropology, and other disciplines.